Development of Translated Questionnaire Malay Subjective Exercise Experience Scale (SEES-M) to Measure Mood Related-Exercise - Ruslan, Nur-Hasanah; Yasin, Siti Munira; Isa, Mohamad Rodi; Mohd Nasir, Nadzimah (Multidisciplinary Applied Research and Innovation, 2022)
Exercise has a positive impact on the physical and mental aspects. The impact should be measured to examine the effectiveness of intervention and rehabilitation. The available instrument in the Malay version is limited and not specific to exercise. Thus, the Malay language instrument is necessary. This study started with translating the Subjective Exercise Experience Scale into Malay (SEES-M) and was followed by a validation study. A cross-sectional study design and purposive sampling were used. The development of this tool involves three types of validity. Content validity involved six experts evaluating each translated item based on four concepts: comprehensiveness, relevance, representation and clarity, using four Likert Scales. Construct validity was determined using Principal Axis Factoring (PAF), an Exploratory Factor Analysis (EFA) oblique rotation method. Concurrent validity was assessed using the Profile of Mood States (POMS). Content validity showed an acceptable content validity index (CVI) (0.92), Item-CVI (0.90), CVI/Ave-Scale (0.90) and concurrent percentage-average excellent value (ACP) (0.87). Construct validity indicates a factor load of over 0.40. The number of items and factors are maintained as the original version. Concurrent validity indicates an excellent relationship between SEES-M and POMS. In conclusion, the SEES-M indicates acceptable validity for assessing mood towards exercise in the Malaysian population. Nonetheless, SEES-M can be retested on athlete populations for future study.